Implementation of Audit Tools and Linked Archive System (ATLAS) on Audit Quality at Public Accounting Firms Registered with OJK in 2024 - Fertha, Fitria; Nurlaily, Liafatra; Fuadi, Fauzan; Aziz, (Rizqi Abdul; Abdiyan, Chaerul Dillah; Kauno, Pangestu (Profesional Muda Cendekia Publishing, 2025)
Research Aims: This research focuses on analyzing the implementation of the ATLAS application using measurement indicators in the EUCS model. Design/methodology/approach: This study used quantitative methods with an accidental sampling technique and a regression model approach. Research Findings: This study shows results that content, accuracy, format, ease of use, and timeless on the ATLAS application have a significant effect on audit quality. This is reinforced with some tests that were conducted that gave a positive number. Theoretical Contribution/Originality: This study's theoretical contribution is to enrich the literature about the role of the ATLAS application in helping the auditor's task to increase the quality of the audits produced, especially in KAPs registered with the OJK. This research also contains effectiveness ATLAS system in increasing auditor reporting. Research limitation and implication: This research is limited to the samples used; however, this study gives a new paradigm about the measurement ATLAS system with the EUCS method.